Bariatric endoscopic-surgical therapies for NAFLD. Should they be considered viable options among current treatments? - Juárez-Hernández, Eva; Velázquez-Alemán, Alain P.; Castro-Narro, Graciela; Uribe, Misael; López-Méndez, Iván (Frontiers in Endocrinology, 2022)
Nowadays, non-alcoholic fatty liver disease is one of the first causes of liver transplant worldwide; many efforts have been done to find the perfect drug for this multifactorial disease. Presently we just have a few drugs that could be used in specific and limited clinical scenarios. Current evidence suggests that bariatric endoscopic and surgical therapies could be strategies with optimal outcomes, with high impact in quality of life, decrease of cardiovascular risk, and improvement in metabolic profile, despite being considered expensive procedures. This review proposes to consider these therapies early together with liver fibrosis evaluation, with long term cost-effectiveness benefits in the absence of response to lifestyle modifications and pharmacological treatments.